Directly observed therapy for clozapine with concomitant methadone prescription: a method for improving adherence and outcome - Pang, Nicholas Tze Ping; Mohamad Isa, Mohd Fadzli; Suarn Singh, Vikram; Masiran, Ruziana (BMJ Group, 2017)
A young male presented with many years of delusions and hallucinations, with concurrent heroin use and subsequent amphetamine uses. There were no depressive or manic symptoms and psychotic symptoms prior to the amphetamine use. After the trials of two atypical antipsychotics and later clozapine due to treatment resistance, adherence and functionality were poor and there was still persistent drug use. As a result, a long acting injectable adjunct was commenced, but only minimal effects were observed. However after initiation of directly observed treatment of clozapine with methadone, there has been functional and clinical response and drug use has ceased.